Influence of mitosporic fungi upon zinc-polymeric coatings on steel under the different environment - Lugauskas, Albinas; Prosyčevas, Igoris; Narkevičius, Algirdas; Selskienė, Aušra; Bučinskienė, Dalia; Ručinskienė, Alma; Binkauskienė, Elena (Journal of Environmental Engineering and Landscape Management, 2013)
Zinc-polymeric coating samples were exposed to different environmental conditions (for 2 years): marine – dunes on the shore of the Baltic Sea (Neringa), rural-agrarian district of Moletai and the industrial zone of Vilnius. During the whole period of the study 94 species of fungi, were isolated from the exposed samples of zinc-polymeric coating on steel. The zinc-polymeric coatings exposed to marine and rural-agrarian environments were deteriorated most markedly. A scanning electron microscope (SEM) was used to characterize the morphology of the surface. The phase composition of the zinc-polymeric coatings on the steel substrate was analysed by an X-ray diffractometer (XRD). The products formed on the zinc-polymeric coatings were detected by a Fourier transformation infrared spectrometer (FTIR). The effect of environmental conditions on the mass change of the samples was determined by the standard dissolution method.First published online: 08 Feb 2013